EFFECT OF LOCAL JOINT FLEXIBILITY (LJF) IN STRUCTURAL ASSESSMENT OF AGEING JACKET OFFSHORE PLATFORM - Azhar, Muhammad Nur Iman (Universiti Teknologi PETRONAS, 2017)
Many fixed steel offshore platforms installed around the globe has exceeded or is approaching the end of design life. In many operating areas, there is an attraction to continue using these ageing facilities dues to continued production or as an adjoining structure to facilitate a new field development or expansion. The structure of the Jacket Type Offshore Platform (JTOP) are mainly connection of tubular members. To justify the life extension of the fixed platforms, various integrity assessment techniques are often used. One of the major techniques used is based on the phenomenon of Local Joint Flexibility (LJF). Although LJF is well known in the offshore industry since the early 1980s, little proven data is available. A static structural analysis has been done using ANSYS software to study the flexibility of the offshore tubular joint in a rigid state. Deformation at the joint and stresses in the members of K -joint are investigated. The joint is assumed to be in flexible condition which is subjected to tension and compression to determine the deformation and stresses.